Effect of marigold leaf on hemoglobin levels on wistar rat expossed cigarette smoking - Fitri Komala Sari; Nur'aini Synthia Maharani; Amilia Yuni Damayanti (University of Darussalam Gontor, 2021)
Background: cigarette smoke is one of the source of free radicals. The influence of free radicals can be suppressed through antioxidant administration. The marigold leaves contain phenolic as antioxidants. This study aims to determine the effect of marigold leaves on hemoglobin levels of the blood of rats exposed to cigarette smoke. Method: the samples were divided into 3 groups (the control group and the treatment group 1 and 2). While the treatment group 1 and 2 were given the exposure to cigarette smoke by giving marigold leaves at a dose of 4.5 grams and 6.3 grams. Blood sampling was carried out on days 0, 7 and 14, measuring the blood sample parameters using the Hematology Analyzer Sysmex KX-21®. Data were analyzed with One Way Anova test, and posthoc the Duncan test. Results: there was a significant effect between the control group against the treatment group 1 and 2 (p <0.05). There were no significant differences between marigold leaves groups with a dose of 4.5 grams and 6.3 in increasing hemoglobin levels (p <1.00). Conclusion: there was significant effect of marigold leaf on hemoglobin levels expossed cigarette smoking at a dose of 4.5 gram and 6.3 gram.